The Role of Human Resource in Laweyan Batik Industry, Surakarta - Edi Kurniadi; Sarwono Sarwono; Asri Laksmi Riani (APMBA (Asia Pacific Management and Business Application), 2018)
Indonesia is a country with a socio-economic structure of society that is represented by the existence of the villages. At present, there are many villages in Indonesia that have developed due to the economic efforts made by the village communities. One of these villages is Laweyan village, in Central Java Province. Laweyan village is a well-known batik production in the development of Surakarta municipality. Up to this day, Kampung Batik Laweyan (Laweyan Batik Village) has become a brand image of batik in Surakarta and surrounding areas, even Laweyan's batik products have penetrated the international world. Here, batik business owner and their employees work together to conserve batik products as a result of the declaration of Kampung Laweyan as batik tourism village. The aim of this study is to develop quality and creativity in batik products, as well as product marketing. To achieve it the improvement of human resource quality (business owner and employee) is needed. Training on various managerial skills and other skills will enable them to compete in the business world as well as to provide better services to customers. Using descriptive analysis, the data is collected using several methods: field observation, interview, FGD, and content analysis (document review). The data is analyzed using several techniques, interactive analysis techniques and internal-external analysis techniques. The results of this study show that the craftsman/business owner in Laweyan batik industrial center always try to maintain the survival of their companies, with the knowledge provided to them and managerial and attitude training, they are better prepared to adapt to the recent development and the environment in the sense that they have developed the integration and synergy of human resources based to the structure and function in batik production and marketing aspect.